2018
DOI: 10.1093/jbcr/irx005
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Burns and Late Spontaneous Artery Ruptures: About Three Cases

Abstract: Electrical burns are responsible for arterial and venous thrombosis, as well as weakening of the arteries. Immediate or delayed arterial occlusions, secondary to the aggression of the intima, or aneurysms, secondary to the aggression of the media, sometimes lead to artery ruptures without any warning signs. Such ruptures may trigger a hemorrhagic shock whose period of onset is variable and unpredictable. We are presenting here three cases treated in our department for electrical burns, whose complications were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Pedicle aps are used to ll in surgical defects [19]. Local skin or musculocutaneous T-and H-shaped aps are used to treat skin defects in the forehead [20]. Rhombic aps, which are local transposition aps, are used to ll defects after skin cancer surgery in the head and neck region [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pedicle aps are used to ll in surgical defects [19]. Local skin or musculocutaneous T-and H-shaped aps are used to treat skin defects in the forehead [20]. Rhombic aps, which are local transposition aps, are used to ll defects after skin cancer surgery in the head and neck region [19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the size of the tumour, the indications for Z-plasty in our series were the absence of superinfection of the tumour, the absence of bony relief making it di cult to mobilise the aps, and the localisation of the tumour in an area where aps can be mobilised. The size of the mobilised aps remains function of the width of the surgical wound [18,20]. However, for vitality of the aps in the Z-plasty that are free, non-pediculised aps, we followed the 2:1 rule, meaning the length should not be more than twice the width.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, with comprehensive consideration by the doctor and the patient's requirements, the patient's right upper arm was amputated. This is because electrical burns can lead to thrombosis of arteries and veins, weakening of arteries, and sometimes rupture of arteries without any warning signs which makes it more difficult to cure (6).…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to pay close attention to and be aware of all possible manifestations and consequences. Several studies have shown that electric burns often requires multiple debridements and skin grafting to repair the wound, often need to prolong the initial treatment and amputation height more frequently, and the amputation rate of electric burns is much higher than that of other burn patients (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%